2013
DOI: 10.1127/0029-5035/2013/0089
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Geastrum (Geastraceae, Basidiomycota) found in Brazil

Abstract: We have studied molecular and morphological data of Geastrum aculeatum sp. nov. and G. echinulatum sp. nov. These two species were found in Brazil's semi-arid region and in central Amazon. It is characterized by the nature of the mycelial layer with aculeate tufts. Geastrum echinulatum differs from G. aculeatum in the size of the spores, presence of subiculum and structural details in the mycelial tufts. The phylogenetic analyses were performed through parsimony and Bayesian methods, using the atp6 and LSU reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
0
22
0
3
Order By: Relevance
“…Douanla-Meli & al. (2005) and Da Silva & al. (2013) analysed nrLSU or a combination of nrLSU and atp6, respectively, to justify the recognition of new species.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Douanla-Meli & al. (2005) and Da Silva & al. (2013) analysed nrLSU or a combination of nrLSU and atp6, respectively, to justify the recognition of new species.…”
mentioning
confidence: 94%
“…Radiigera contains three Nearctic and one Palearctic (Domínguez de Toledo & Castellano, 1996), plus one paleotropical species (Orihara & al., 2008). Previous phylogenetic analyses in the order Geastrales have shown Radiigera specimens to be nested in Geastrum (Hosaka & al., 2007;Hosaka & Castellano, 2008;Da Silva & al., 2013), but none of these studies was specifically focused on the relationship between the two genera. However, Jeppson & al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, only around 1000 species of macrofungi have been described for the Amazon forests [3]. For gasteroid fungi, 20 species have been described distributed in the states of Amazônia, Pará and Rondônia [15,16,17,18,19,20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…(2006), by means of molecular studies, showed the close relationship between the earthstars and the members of a "gomphoid-phalloid clade" and proposed the order Geastrales Hosaka & Castellano. In the last 12 years, this genus has been widely studied in the northeastern Brazil (Baseia & Milanez, 2002;Baseia & Calonge, 2006;Fazolino & al., 2008;Silva & al., 2013;Cabral & al., 2014aCabral & al., , 2014bSousa & al., 2014a, c, d), although there is a lack of information about it for the southeastern regions, specially for Minas Gerais.…”
Section: Introductionmentioning
confidence: 99%